Physical Motor Development of Primary School Age Children in The Learning Process - Nurcahyani Br Ginting, Indah; Aulia, Nurul (International Journal of Students Education, 2023)
This research aims to determine the physical motor development of children at the Muhammadiyah Karangbendo Elementary School. This research uses descriptive qualitative methods with data acquisition based on observation, interview and documentation techniques. The subjects of this research were students consisting of 28 people. The data analysis techniques in this research use pre-field analysis and field analysis using the Miles and Hubermen model which includes data reduction, data display and conclusion drawing. Based on the research results, it can be explained that simultaneously in the learning process it can be seen that all students have different physical motoric developments and these developments continue to occur and change according to students’ learning activities. The world of children is the world of play, when they play children will absorb everything that happens in the surrounding environment, as stated by Maslichatoen that "play is also an essential demand and need for elementary school age children, through play activities children will be able to achieve the demands and development needs of the dimensions of motor, cognitive, creativity, language, emotion, social, values and attitudes to life. This is in line with Tri Murti’s research, which explains that elementary school children’s motor skills are in line with their physical growth. They are able to control themselves to perform more coordinated motor skills. They are able to perform gross motor skills such as throwing a ball, catching a ball, running, standing on one leg, jumping, riding a bicycle and swimming. They are also able to perform fine motor skills, such as writing, drawing and embroidering or sewing.